The process capability model for governance of the Election Organizer Ethics Court system - Syopiansyah Jaya Putra (JOIN (Jurnal Online Informatika), 2018)
The capability level assesment for governance of the Election Organizer Ethics Court Information System [SIPEPP] is necessary to ensure strategic planning allignment, value delivery, risk management, resources management and performance measurement. SIPEPP implementation has special problems in optimizing human resources and weak supervision management, so it is important to asess capability levels to provide solutions to these problems. The purpose of this paper is to assess the current and expected capability level conditions, gap analysis and recommendations for SIPEPP good governance. This research method uses the Process Assessment Model (PAM) from Control Objectives for Information and Related Technology (COBIT 5) which consists of stages of initiation, planning the assessment, briefing, data collection, data validation, process attribute level, and result and recommendation. The results of this study indicate the level of optimization of resources and performance monitoring processes are level 2 (Managed Process) which means that the process has been recorded, measured and in accordance with the objectives. The process of managing human resources, assets and operations are at level 1 (Performed Process), meaning that both processes have been applied to SIPEPP governance. Recommendations related human resources are the selection of appropriate human resources by involving management, while related assets require a priority list of implementation systems, and related supervision requires detailed monitoring schedules. This study result can be taken into consideration for improving good governance of SIPEPP implementation.